In Vivo Self‐Assembly Induced Cell Membrane Phase Separation for Improved Peptide Drug Internalization - Guo, Ruo‐Chen; Zhang, Xue‐Hao; Fan, Peng‐Sheng; Song, Ben‐Li; Li, Zhi‐Xiang; Duan, Zhong‐Yu; Qiao, Zeng‐Ying; Wang, Hao (Angewandte Chemie International Edition, 2021)
Therapeutic peptides have been widely concerned, but their efficacy is limited by the inability to penetrate cell membranes, which is a key bottleneck in peptide drugs delivery. Herein, an in vivo self‐assembly strategy is developed to induce phase separation of cell membrane that improves the peptide drugs internalization. A phosphopeptide KYp is synthesized, containing an anticancer peptide [KLAKLAK]2 (K) and a responsive moiety phosphorylated Y (Yp). After interacting with alkaline phosphatase (ALP), KYp can be dephosphorylated and self‐assembles in situ, which induces the aggregation of ALP and the protein‐lipid phase separation on cell membrane. Consequently, KYp internalization is 2‐fold enhanced compared to non‐responsive peptide, and IC50 value of KYp is approximately 5 times lower than that of free peptide. Therefore, the in vivo self‐assembly induced phase separation on cell membrane promises a new strategy to improve the drug delivery efficacy in cancer therapy. An in vivo self‐assembly strategy is developed to induce phase separation of cell membrane that improves the peptide drugs internalization and anticancer efficacy. KYp self‐assembles in situ, which induces the aggregation of ALP and the protein‐lipid phase separation and leakage on the cell membrane. The peptide drugs internalization is 2‐fold enhanced compared to non‐responsive peptide nanoparticle.